Promoting the Diamond Suite and President Suite of Rich Palace Hotel Using a Promotional Video - Poh Vania Lokita (Kata Kita: Journal of Language, Literature, and Teaching, 2018)
The main problem that Rich Palace Hotel is currently facing is the Diamond suites and Platinum President suites are not selling very well. The occupancy of both rooms are very low which is only 5%-8% per month. Therefore,making a promotionaltool with videoformwould be the right solution tosolve the problem.  By watching promotionalvideo customers will know more about Diamond suites and President suites,  because promotional video contains information that can increase customers awareness of the The Diamond suite and President suite. It canalso become the tool for the sales and marketing team to offer both rooms in order to increase the occupancy level. The video will show about the benefits of staying in Diamond Suites or Platinum President Suites compared to staying at the Deluxe room.